Which expression is equivalent to the expression below? StartFraction m + 3 Over m squared minus 16 EndFraction divided by Start

Question

Which expression is equivalent to the expression below?

StartFraction m + 3 Over m squared minus 16 EndFraction divided by StartFraction m squared minus 9 Over m + 4 EndFraction

in progress 0
Alice 2 weeks 2021-11-20T16:39:58+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-11-20T16:41:05+00:00

    Answer:

    It’s actually B – \frac{1}{(m-4)(m-3)}

    Step-by-step explanation:

    Edg2020

    0
    2021-11-20T16:41:17+00:00

    Step-by-step explanation:

     \frac{m + 3}{ {m}^{2}  - 16}  \div  \frac{ {m}^{2} - 9 }{m + 4}  \\  \\  =  \frac{m + 3}{ {m}^{2}  -  {4}^{2} }  \div  \frac{ {m}^{2} -  {3}^{2}  }{m + 4}   \\  \\  = \frac{m + 3}{ ({m} + 4)(m -  {4})}  \div  \frac{ ({m} + 3)(m-  {3}) }{m + 4}  \\  \\ = \frac{m + 3}{ ({m} + 4)(m -  {4})}   \times   \frac{ m + 4 }{({m} + 3)(m-  {3})}  \\  \\  = \frac{1}{ (m -  {4})}   \times   \frac{ 1}{(m-  {3})}  \\  \\  = \frac{1 \times 1}{ (m -  {4}) \times (m-  {3})}   \\  \\  = \frac{1}{ m^{2}  + ( - 4 - 3)m + ( - 4)( - 3)}  \\  \\  = \frac{1}{ m^{2}  + ( - 7)m + 12}  \\  \\  = \frac{1}{ m^{2}   - 7m + 12}

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )